Analisis Penerapan Metode Six Sigma terhadap Penurunan Produk Cacat pada Proses Produksi Netaly Boutique di Kota Bandung - Siti Fatimah; Resi Juariah Susanto (PPIMAN Pusat Publikasi Ilmu Manajemen, 2026)
Netaly Boutique is a business operating in the fashion industry that still encounters product defects, including untidy stitching, incorrect garment sizes, and poor finishing quality. These issues lead to increased material waste and production costs, highlighting the need for a more effective quality control system. This study aims to analyze the implementation of the Six Sigma method in reducing product defects during the production process at Netaly Boutique in Bandung City. This research employed a descriptive method with a quantitative approach. The data were collected through observation, interviews, documentation, and production data from January to December 2025. The analysis was conducted using the Six Sigma method through the Define, Measure, Analyze, Improve, and Control (DMAIC) stages. The results showed that, out of a total production of 16,350 units, 1,119 defective products were identified, with the three dominant types of defects being untidy stitching (35.03%), incorrect garment sizes (33.16%), and poor finishing quality (31.81%). The average Defects Per Million Opportunities (DPMO) before improvement was 22,830, with a sigma level of 3.52. After implementing the proposed improvements, the DPMO decreased to 9,120, while the sigma level increased to 3.95. These findings indicate that the implementation of the Six Sigma method effectively reduced product defects and improved the effectiveness of quality control in the production process at Netaly Boutique.